Address by the United States Secretary of Education to the Annual Convention of the American Vocational Association - Bennett, William J.; Department of Education, Washington, DC. Office of the Secretary ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The educational system of the United States reflects U.S. respect for both diversity and equality. Differences in students' aspirations are accommodated by offering both precollegiate and vocational education. Three essential major purposes of education are the civic, the personal, and the utilitarian. Where the civic and personal ends of education are concerned, Americans have essentially the same goals for all students. When the utilitarian ends of education are considered, more serious disagreement over curricula arises. The utilitarian ends of education are governed more by considerations of diversity. Two rival views exist regarding students choosing employment requiring less than a baccalaureate degree. One holds that what the employment-bound student needs is academic rigor; the other, that academics are not important but training in a trade is. A new consensus among educators and employers lies in the middle: the utilitarian function of school is to assist in preparing all students for that 40-year sequence of events following graduation--for different employers, different jobs, and different trades. Three sets of attributes are needed: general skills, general knowledge, and worthy values and habits. The main objective of learning in schools must be the same for all students; differences in educational programs must never invite distinctions of citizenship. (YLB)
ERIC Note: Paper presented at the American Vocational Association Convention (Atlanta, GA, December 6, 1985).
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Objectives; Educational Principles; Outcomes of Education; Role of Education; Secondary Education; Vocational Education; Opinion Papers; Speeches/Meeting Papers